Barriers to Emergency Obstetric Care (EOC) and birth practices in rural Manikganj - Gazi, Rukhsana; Goodbum, Liz; Chowdhury, A Mushtaque R; Karim, Fazlul (BRAC Research and Evaluation Division (RED), 2019)
This study aimed to explore the situation during delivery in rural homes and to identify the barriers to emergency obstetric care (EOC). Twenty sO< pregnant women were followed-up at home by experienced female interviewers. No notes were taken during the conversations but a detailed diary of each visit was made immediately after they returned to the base. Women themselves were often not aware of self care. A fear of sin which was attributed to the presence of unknown male doctors in the hospital acted as barrier. Women's relationship with their in-laws was found to be important. An early assessment and indication for referral by traditional birth attendants (TBAs) was important in the decision making process. TBAs were often trying to manage the complications by themselves. The hospital is a unfamiliar place for rural people. A common perception was that the hospital people pay attention only to rich and educated people. In-laws and neighbours jointly undertook the decision for hospitalization. All members of the community need to be educated about the danger signs of obstetric emergencies. For this poster charts, audio visual aids, folk drama might be used as effective tools for the information campaign. TBA training interventions should give more emphasis to early recognition of complications and early indications for referral.